2014
DOI: 10.1021/jm501532z
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of BI 207524, an Indole Diamide NS5B Thumb Pocket 1 Inhibitor with Improved Potency for the Potential Treatment of Chronic Hepatitis C Virus Infection

Abstract: The development of interferon-free regimens for the treatment of chronic HCV infection constitutes a preferred option that is expected in the future to provide patients with improved efficacy, better tolerability, and reduced risk for emergence of drug-resistant virus. We have pursued non-nucleoside NS5B polymerase allosteric inhibitors as combination partners with other direct acting antivirals (DAAs) having a complementary mechanism of action. Herein, we describe the discovery of a potent follow-up compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…[101] Numerous efforts to produce antivirals have been made, but room for improvement is still vast. Beaulieu and co-workers [102] have actively investigated allosteric inhibitors of the main viral RNA polymerase non-structural protein 5B (NS5B) in one of its pockets "Thumb 1" vital to its RNA synthesis abilities. In an effort to late stage optimize known inhibitors the authors found that substituted indole-cinnamic acid derivatives were optimal for this goal (Figure 27).…”
Section: Cyclobutanes In Antiviral Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[101] Numerous efforts to produce antivirals have been made, but room for improvement is still vast. Beaulieu and co-workers [102] have actively investigated allosteric inhibitors of the main viral RNA polymerase non-structural protein 5B (NS5B) in one of its pockets "Thumb 1" vital to its RNA synthesis abilities. In an effort to late stage optimize known inhibitors the authors found that substituted indole-cinnamic acid derivatives were optimal for this goal (Figure 27).…”
Section: Cyclobutanes In Antiviral Compoundsmentioning
confidence: 99%
“…However, its unique structure and properties as demonstrated in this review and continuous efforts in synthesis methods might render it a prominent member in the medicinal chemist's toolbox in the not-toodistant future. Absorption and plasma levels Increased NS5B Thumb pocket 1 inhibitor [102,103] Hepatitis C 5-HT6R antagonists [117] Schizophrenia Cytotoxicity Lowered Anti-leishmanial [120] Visceral Leishmaniasis Mycobacterium toxicity Increased Anti Mtb and Map mycobacterials [124,125]…”
Section: Reduction Of Planaritymentioning
confidence: 99%
“…25 [80,81]. An indole analogue BI 207524 (165, EC 50¼ 11 & 29 nM) was discovered as a potent HCV NS5B polymerase thumb pocket 1 inhibitor, the pharmacokinetics profile with respect to clearance of the compound is very low and later its clinical investigation has been halted [82]. The genotoxicity of the clinical candidate BI 207524 further reduced by the structural alterations and this ideology afforded non-genotoxic HCV NS5B thumb site I inhibitor (165, EC 50¼ 27 & 14 nM) [83].…”
Section: Recent Patent Updates On Hcv Inhibitorsmentioning
confidence: 99%
“…Amidst them, heterocycles with polycyclic ring system possess distinct rigid geometry displaying high functional specialization by orienting its substituents in three dimensional spaces, there by attracting great interest [2]. Indole is a bicyclic heterocyclic scaffold that find applications in medical therapy due to a variety of valuable biologic activities such as antiviral [3,4], antiinflammatory [5,6], anti-hyperlipidemic, antihypoglycemic, anti-hypertensive, anti-asthmatic, anti HIV [7], antidepressant [8] and notably anticancer [9][10][11][12][13][14][15] activity. Few marketed anticancer indole derivatives are vincristine, vinblastine, vinorelbine, vindesine, mitraphylline, cediranib and apaziquone [2].…”
Section: Introductionmentioning
confidence: 99%